Communication for Sangha’s Administration to Society - ฐิตปุญโญ พระครูไพศาลวัฒนคุณ (Journal of Educational Review Faculty of Education in MCU, 2018)
All six sections of Sangha administration: government, religious education, social welfare, propagation, public assistance and public welfare, are real social welfare. That makes Sangha organization recognized in gratitude to public. But the information of Sangha’s work reaches few people. It is necessary to manage the Sangha’s communication systematically. The communication management system of Sangha must consist of specific purpose, qualified sender, useful message, suitable channel, target receiver and feedback evaluation. Communication system is used in parallel with a valid management system, i.e. POSDC Model for Planning, Organizing, Staffing, Directing, and Controlling. These processes should be implemented in Sangha’s organizations, temples and communities. The results of good management in communication system of Sangha will make a good perception of society, good understanding of public and good co-operation in Sangha’s affairs.